O atendimento socio individual ao segmento masculino no Serviço Social - Borges, Renan Barateli (2022)
The present dissertation aims to study the professional practice of social workers, facing the challenges and demands presented by the male segment in their daily intervention. The main objective here is to analyze and comprehend which demands, material and subjective, presented by the male segment to the social service. In this way, we have analyzed the professional practice in services typified by the social policy of social assistance and health policy in the city of Campinas/SP. From a theoretical point of view, we have provoked important reflections on the categories of gender, race and class, as structuring devices in the constitution of social inequality in Brazil. From the dialogue with Michel Foucault, Bell Hooks and Judith Butler, we comprehend the socially constructed place, defined and occupied by this male subject in the West. Through the studies of Sandra Eloiza Paulino and Maria Lucia Rodrigues, we observe the challenges of the practice of social workers in their daily lives from a socio-individual approach. The methodological procedures were based on a qualitative study, structured by reflective analysis of the bibliographic material collected, and correlated with professional practice. We collected this material through five individual interviews with social workers. The main results point to a lack of professional training regarding the socio-individual approach, as well as technical-operative and methodological challenges regarding subjective needs. Significant concerns are expressed in the construction of professional practice in contemporary times, as it has been exercising a racist, heterosexist and classist reading from a different guise and performance, even with theoretical advances provoked by the immersion in the Marxist method, when it disregards important reflections on the complexity of social and human life